SIRT6 Inhibitor, OSS_128167 Restricts Hepatitis B Virus Transcription and Replication Through Targeting Transcription Factor Peroxisome Proliferator-Activated Receptors α - Jiang, Hui; Cheng, Sheng-Tao; Ren, Ji-Hua; Ren, Fang; Yu, Hai-Bo; Wang, Qing; Huang, Ai-Long; Chen, Juan (Frontiers in Pharmacology, 2019)
Hepatitis B virus (HBV) is a major public health threat and anti-HBV drugs are limited to nucleos(t)ide analogs (NAs) and pegylated interferon alpha (Peg-IFNα). Towards identifying an effective compound for HBV treatment is important to suppress and eradicate HBV. In this study, we explored the anti-viral effect of Sirtuin 6 (SIRT6) inhibitor, OSS_128167, in HBV transcription and replication. Firstly, we found that OSS_128167 could decrease the level of HBV core DNA and 3.5-Kb RNA in vitro. Furthermore, the level of HBV DNA and 3.5-Kb RNA were also markedly suppressed by OSS_128167 administration in HBV transgenic mice. In addition, we found that depletion of SIRT6 inhibited HBV transcription and replication in HepG2.2.15 and HBV-infected HepG2-NTCP cells, whereas overexpression of SIRT6 enhanced HBV transcription and replication. Importantly, the positive effect of SIRT6 overexpression on HBV transcription could be blocked by OSS_128167 treatment. Further mechanism studies showed that HBV core promoter was significantly activated by SIRT6 through upregulating peroxisome proliferator-activated receptors α (PPARα) expression. And ectopical expression of SIRT6 or PPARα relieved the restriction of HBV transcription mediated by OSS_128167. In summary, our results showed that OSS_128167 might serve as a potential antiviral agent for HBV therapy and SIRT6 played a pivotal role in HBV transcription and replication.